Considerations for Creating the UNFCCC Online Portal for Climate Action in Agriculture & Food Security - Mugo, Cynthia; Cramer, Laura K.; Nendo Advisory (International Livestock Research Institute, 2023)
A survey was conducted among 52 representatives of the African Group of Negotiators Experts Support. From this survey, the members voted that the UNFCCC online portal on climate action in food security and agriculture should have the following objectives (in the order of the highest number of respondents saying it is an objective) - information sharing, raising awareness of climate action in agriculture, and aiding fundraising. From the survey, the most eligible publishers for the online portal were national focal points, followed by research organizations and UNFCCC observer organizations. It appears the gap is that there is no generally accepted definition of an online portal. Some websites (which, upon inspection, are online portals) classify themselves as dashboards or databases. There’s room to create a shared definition and publicise this for other United Nations bodies and other organisations. Upon evaluation, the African Group of Negotiators Experts Support ought to proceed with the following recommendation areas: Mobile-First: this refers to an expectation to build the online portal to have some features (for example, viewing and manipulating data) compatible with basic Android smartphones. The desired metric is that the online portal scores at least 90/100 in Google’s PageSpeed Insights test. Accessibility: this will be a critical component of the online portal, focusing on ensuring it is compliant for voice-to-text accessibility for website visitors with literacy or usability challenges. Training and Visual Assets: this refers to the capacity building module – giving access to various forms of training and professional development available on the online portal. Visual assets aim for infographics, motion graphics, and data visualisation to market and raise awareness of the online portal and its contents.